Perspectives of employees on the effectiveness of performance management at a selected chemical plant in the Free State province, South Africa - Gare, Tshepo (University of the Witwatersrand, Johannesburg, 2024)
Purpose – Concerns about the effectiveness of performance management have led researchers to explore several ways of measuring it. Despite extensive research, there is a gap in understanding how employees perceive performance management systems, particularly in the chemical industry in the Free State province, South Africa. This study aims to assess the effectiveness of performance management at a selected chemical plant from employees’ perspectives, focusing on critical factors such as accuracy, fairness, and management transparency. Design/method/approach – A qualitative research method was employed. Interviews were conducted with employees from various occupational backgrounds to gather in-depth insights into their views on the performance management process. Findings – The study found that employees perceived the performance management system as generally effective but highlighted areas needing improvement, particularly in terms of transparency and fairness. Employees valued accuracy in performance assessments but expressed concerns about potential biases and lack of clear communication from management. Research limitations/implications – This study is limited to a single chemical plant in the Free State province, which may not be representative of the entire chemical industry. However, the findings provide a foundation for future research in other chemical plants and similar industrial settings. Contribution – This study contributes to the existing literature by providing empirical evidence on employees’ perceptions of performance management in the chemical industry in South Africa. It highlights the importance of management transparency and fairness in enhancing the effectiveness of performance management systems.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administrationto the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Performance Management (PM); Accuracy; Fairness; Effectiveness; Transparency; UCTD; SDG-8: Decent work and economic growth